2007
DOI: 10.1128/aac.00116-07
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of Acyclovir after Intravenous Infusion of Acyclovir and after Oral Administration of Acyclovir and Its Prodrug Valacyclovir in Healthy Adult Horses

Abstract: The purpose of this study was twofold. The first aim was to evaluate the oral bioavailability and pharmacokinetics (PKs) of acyclovir in horses after intravenous (i.v.) administration and after oral administration of acyclovir and its prodrug, valacyclovir. Second, we aimed to combine these PK data with pharmacodynamic (PD) information, i.e., 50% effective concentrations (EC 50 values) from in vitro studies, to design an optimal dosage schedule. Three treatments were administered to healthy adult horses: 10 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
85
1
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(90 citation statements)
references
References 24 publications
3
85
1
1
Order By: Relevance
“…However, the severe and progressive clinical course suggests a poor efficacy of acyclovir administered orally in the horse, as previously reported. 5,6,16 On the other hand, steroid therapy could have induced an immunosuppression, facilitating viral replication.…”
mentioning
confidence: 99%
“…However, the severe and progressive clinical course suggests a poor efficacy of acyclovir administered orally in the horse, as previously reported. 5,6,16 On the other hand, steroid therapy could have induced an immunosuppression, facilitating viral replication.…”
mentioning
confidence: 99%
“…The percentage of human intestinal absorption (% HIA) for selected prodrugs and precursors was obtained from pharmacokinetic data previously reported (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) and well-known databanks (29-31). The classification based on % HIA, previously reported by Zhao et al (24), was used to score the absorption profile of prodrugs and precursors as high, moderate and low (see Table 1).…”
Section: Drugs and Prodrugs Selectionmentioning
confidence: 99%
“…The antiherpesvirus drug acyclovir has been used for the treatment of EHV-1-associated neurological disorders [13,20,36]. Oral administration is preferable to intravenous infusion during outbreaks, but pharmacokinetic studies have revealed that acyclovir given orally to horses is poorly bioavailable and reaches low plasma concentrations [4,15,35] that do not exceed the 50% effective concentration (EC 50 ) against EHV-1 strains, as determined by in vitro plaque reduction assay [16]. In contrast, oral administration of valacyclovir, the prodrug of acyclovir, achieves concentrations within the sensitivity range of EHV-1 [15,23].…”
mentioning
confidence: 99%
“…Oral administration is preferable to intravenous infusion during outbreaks, but pharmacokinetic studies have revealed that acyclovir given orally to horses is poorly bioavailable and reaches low plasma concentrations [4,15,35] that do not exceed the 50% effective concentration (EC 50 ) against EHV-1 strains, as determined by in vitro plaque reduction assay [16]. In contrast, oral administration of valacyclovir, the prodrug of acyclovir, achieves concentrations within the sensitivity range of EHV-1 [15,23]. Therefore, valacyclovir is now considered to be an attractive candidate for treatment of EHV-1-associated neurological disorders, even though its therapeutic efficacy has not been proven in a controlled study.…”
mentioning
confidence: 99%
See 1 more Smart Citation